Analisis Kendala Pembelajaran Kata Bantu Bilangan Bahasa Mandarin Beserta Solusinya - Rosemary Sylvia (Bina Nusantara University, 2008)
For foreigner, Mandarin language numeral words are very dificult to be mastered. Students of Bina Nusantara University are also having difficulties in learning the Mandarin language numeral words. Hopefully using quiz and questioner able to find the dificultioes faced by the students of Bina Nusantara University in learning Mandarin language numeral words. Also using questioner and interview to find the solustions. The research object is Chinese students of Bina Nusantara University from 2-4 semesters. Result from the data analysis is the student did not master well of the Mandarin language numeral words. The student time study in Bina Nusantara University did not have much effect on the student mastering of the Mandarin language numeral words. What causing the student having difficulties in learning the Mandarin language numeral words are because the numeral words in Mandarin language is too much also the usage is very wide.